Sistema integrado de informações e gestão ambiental: proposta de análise ambiental e ordenamento das paisagens aplicado ao licenciamento ambiental em órgãos públicos do Brasil - Correia, Luiz José de Almeida (2014)
Since the first evidence of the occurrence of human settlements on earth until our days, there has been a constant and increasingly exploitation of natural resources, which has cause, very often an irreversible process of the environmental degradation. In Brazil, such processes that are intrinsically linked to the exploratory systems done originally by first colonization settlers, which were markedly by exceeding the carrying capacity of natural environments and recover shape. Thus, the growing of economic development associated with urban expansion and technological development, leveraged, over the years, there were a need for creation, especially by the government, institutions, technical and legal instruments, action plans and territorial organization of programs to establish measures and standards for environmental protection, in order to ensure the quality of life for the society. The Brazilian environmental policy has highlighted its connection only after the 1980s, and then the environmental laws created with greater awareness and severity, driven by global environmental awareness. Despite the of public and institutional framework which has been created, still there deficiencies perceived on creation, definition and/or compliance of the mechanisms of environmental control and processes itself. The decision support systems, geographic information systems and environmental management systems, among others, emerge as indispensable tools for real knowledge and mastery of the natural potential of the environments and their ability to function in support of established uses. Based on the foregoing, we established the focus of this research as is it follows, to contribute to the integrated environmental management of federal, state or local agencies, in reliance on the development of an "Integrated Information System and Environmental Management - SIIGA" structured based on a GIS platform to be applied on licensing, monitoring and environmental monitoring activities, by the use of the geo supported by environmental, legal and information and communication technology concepts. The SIIGA was therefore developed to allow the inter-relationship of three basic components - the procedures adopted in the process of "Environmental Analysis", all "legal apparatus" of environmental legislation and the development of an application involving "Computer Systems". After been developed and tested, the SIIGA show its potential for an efficient and effective for integrated and participatory environmental management environmental public institutions, bringing strategic and economicbenefits, and compile in one database, which can provide spatial information and are more robust and integrated analyzes on management of projects and activities using environmental resources of the State. Finally, it’s noted that this study sheds important contribution to the development of a truly participatory process of environmental management, as recommended in the Brazilian environmental legislation and desired by society.